ACCOUNTING CORRECTIONS. - Dixon, Robert L.; Hill, Thomas M.; Lanterman, Joseph B.; Mautz, Robert K.; McMullen, Stewart Y.; Moonitz, Maurice; Stans, Maurice H. (The Accounting Review, 1954)
Abstract This article discusses the information on the paragraph no. 5. The Paragraph No. 5 under "Expense" in the 1948 Revision of Accounting Concepts and Standards Underlying Corporate Financial Statements of the U.S. reads that An assignment of all or a portion of the cost of an asset to expense, made in good faith after considered judgment and after competent review, in accordance with the accounting concepts and standards of the time, is not subject to reversal in a later period. Errors of a mechanical and non-judgment nature should be corrected in the period of their discovery. The Committee on Concepts and Standards is in agreement with the apparent basic purpose of this statement to reduce the possibility of manipulation of the net income calculation through reversals, revisions and reaccounting of past depredation charges and other amortizations. At the same time it recognizes that a position unalterably opposed to the correction of errors of judgment is both arbitrary and difficult to defend.